2010
DOI: 10.1021/jf903488b
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pasteurization, Spray- and Freeze-Drying, and Storage on the Carotenoid Content in Egg Yolk

Abstract: A liquid chromatography-atmospheric pressure chemical ionization mass spectrometry [LC-(APCI)MS] method was developed to identify and quantify the carotenoids present in fresh, pasteurized, and freeze- and spray-dried egg yolk in two independent batches. The egg yolk powders in each batch were stored in the dark for 6 months at -18 or 20 degrees C. Carotenoids were isolated by solvent extraction without saponification and analyzed by HPLC using a C(30) column coupled to a photodiode array and mass detector. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 31 publications
0
29
0
3
Order By: Relevance
“…Research techniques for the fast determination or analysis of carotenoids continue to be reported by range of researchers. These techniques include high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), liquid chromatography-tandem mass spectrometry (LC-MS/MS), and ultra-high performance liquid chromatography (UHPLC) (Brulc et al, 2013;Kopec, Cooperstone, Cichon, & Schwartz, 2012;Machmudah & Goto, 2013;Ow, Salim, Noirel, Evans, & Wright, 2011;Rivera & Canela-Garayoa, 2012;Swartz, 2005;Wenzel, Seuss-Baum, & Schlich, 2010. Brief details and application of these techniques are given here.…”
Section: Analysis Of Egg Carotenoidsmentioning
confidence: 99%
“…Research techniques for the fast determination or analysis of carotenoids continue to be reported by range of researchers. These techniques include high-performance liquid chromatography (HPLC), liquid chromatography-mass spectrometry (LC-MS), liquid chromatography-tandem mass spectrometry (LC-MS/MS), and ultra-high performance liquid chromatography (UHPLC) (Brulc et al, 2013;Kopec, Cooperstone, Cichon, & Schwartz, 2012;Machmudah & Goto, 2013;Ow, Salim, Noirel, Evans, & Wright, 2011;Rivera & Canela-Garayoa, 2012;Swartz, 2005;Wenzel, Seuss-Baum, & Schlich, 2010. Brief details and application of these techniques are given here.…”
Section: Analysis Of Egg Carotenoidsmentioning
confidence: 99%
“…At the end of 6 months of storage about 38% loss in carotenoid content was recorded. Wenzel et al (2010) reported, after the 6 months of storage, the contents of carotenoids in the egg yolk powder were significantly lower. Similar observations were made by Tavarini et al (2007) (Pesek and Wilson 1986), degree of exposure to light (Kim et al 2002) and interaction of ingredients (Osuna-Garcia et al 1997).…”
Section: Resultsmentioning
confidence: 96%
“…In comparison to the previous techniques for determining xanthophylls in egg yolk samples [18][19][20], the procedure used in this study is an easy and small-scale technique that minimizes organic solvent consumption in the preparation of AX, CX, and ACAEE. The extract obtained by the extracting operation was purified by subsequent centrifugal monolithic silica spin mini-column, MonoSpin ® -SI.…”
Section: Sample Preparation-application Of Centrifugal Spin Mini-columnmentioning
confidence: 99%
“…Without regard for industrial nations and developing countries, the optimal harmonized method for chemical monitoring in foods must be simple, small scale, economical in time and cost, and must cause negligible harm to the environment and analysts. Several techniques based on high-performance liquid chromatography (HPLC) for the quantification of xanthophylls in egg yolk samples have been reported [18][19][20][21]. However, these methods cannot detect simultaneous AX, CX, and ACAEE; and they involve several analytical steps in the sample preparation, which are time-and cost-consuming and do not permit the determination of a large number of samples.…”
Section: Introductionmentioning
confidence: 99%